Aberrant B cell responses as drivers of autoantibody generation and epitope diversification in SLE pathogenesis - Tariq, Fareeha; Charavanmuttu, Yathavi; Labiba, Kazi; Wincup, Chris (Frontiers in Immunology, 2026)
Systemic lupus erythematosus (SLE) is a prototypic systemic autoimmune disease characterised by loss of tolerance, widespread immune dysregulation, and production of diverse autoantibodies (typically directed against nuclear components). A central mechanism underlying this diversification of autoantibodies is epitope spreading, where immune responses directed against primary antigen-derived epitope progressively evolve to recognise additional epitopes, thereby perpetuating autoimmune pathology. Evidence from murine models and longitudinal human studies demonstrate that autoreactive B cells are central to this process, functioning both as antibody producers and antigen-presenting cells that sustain T cell responses. Special pockets within secondary lymphoid organs such as extrafollicular regions and germinal centres are the breeding ground for autoreactive B cell repertoire diversification, while tertiary lymphoid structures (TLS) provide tissue-specific niches for in situ diversification, particularly in lupus nephritis and cutaneous lupus. These aberrant B cell responses not only perpetuate autoantibody production but also shape organ-specific pathology. From a therapeutic perspective, rituximab and other anti-CD20 monoclonal antibody therapies deplete circulating B cells but may fail to eliminate plasma cells or fully dismantle TLS, allowing diversification to persist and disease relapses to occur. Early-phase studies of CD19-directed CAR-T therapy has shown potent depletion of naïve and memory B cells with partial reconstitution of predominantly naïve repertoires; however, long-lived plasma cells (LLPCs) and certain pathogenic subsets remain unaffected, leaving the potential for relapse. Dual-target CD19/BCMA CAR-T approaches overcome these limitations by additionally depleting plasma cells, eliminating pre-existing autoreactive clones, and reducing inflammatory pathways, offering a more comprehensive reset of B-cell-driven autoimmunity. Epitope spreading thus represents both a driver of chronic autoimmunity and a therapeutic target, highlighting the need for interventions that precisely disrupt autoreactive B-cell networks while preserving immune function.